Dari Pesisir ke Muka Bumi: Bagaimana Kearifan Lokal dan Teknologi Modern Bersinergi untuk Melestarikan Laut Keanekaragaman Hayati Laut - NusaPutri, Yusriana (Maliki Interdisciplinary Journal, 2025)
Conservation of marine resources and engagement of coastal communities through strategic environmental education. Emphasise the importance of integrating local wisdom in coastal and marine resource management to promote a sustainable balance between ecological integrity and resource utilisation. To develop comprehensive and sustainable management models, future conservation initiatives should revitalise traditional practices while integrating modern scientific findings. Additionally, the importance of mangrove ecosystems was underlined, with alarming statistics showing substantial degradation. A bottom-up approach to mangrove restoration, which emphasises the involvement of local communities as active stewards of the environment. This method aims to foster a sense of ownership, creating social mechanisms that encourage protective action against destructive activities.